Are professional soccer players at higher risk for ALS?. Issue 7 (December 2013) - Beghi, Ettore
Abstract: Since the observation of several deaths from amyotrophic lateral sclerosis (ALS) among Italian professional soccer players, an association between ALS and soccer has been postulated, supported by high rates of morbidity and mortality risks in large cohorts of professionals. Several factors may explain this. A history of repeated (head) injuries is reported more frequently by ALS patients than by individuals with other clinical conditions. An association between exercise and ALS has also been suggested, but results in animals and humans are conflicting. Some clinical and experimental observations suggest a relation between ALS and use of substances such as non-steroidal anti-inflammatory agents, and dietary supplements including branched-chain amino acids. Although Italian soccer players may be at higher risk of ALS than players in other countries, and higher than expected disease frequency seems soccer-specific, increased attention by the Italian lay press is an explanation that cannot be excluded. However, growing evidence points to the possibility that soccer players with ALS are susceptible individuals who develop the disease in response to combinations of environmental factors. Only cohort and case-control studies carried out with the same design in different European countries can provide a definite answer to this suspected but still unconfirmed association.